2013
DOI: 10.1136/archdischild-2012-303386
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional content of infant commercial weaning foods in the UK

Abstract: The UK infant food market mainly supplies sweet, soft, spoonable foods targeted from age 4 months. The majority of products had energy content similar to breast milk and would not serve the intended purpose of enhancing the nutrient density and diversity of taste and texture in infants' diets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
87
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 18 publications
7
87
2
2
Order By: Relevance
“…This could be due to the specific combination of ingredients that may mask or interfere with learning about the particular flavor of single vegetables [28]. In support of this argument, Garcia et al [13] investigation of commercially available infant foods in the UK found that 8.5% of savory products also had added fruit, giving them a sweet taste. Conversely in a lowincome sample of infants who received commercial baby foods free of charge as part of a national public health initiative in the US, those who consumed commercial baby food consumed a greater variety of fruits and vegetables [37].…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…This could be due to the specific combination of ingredients that may mask or interfere with learning about the particular flavor of single vegetables [28]. In support of this argument, Garcia et al [13] investigation of commercially available infant foods in the UK found that 8.5% of savory products also had added fruit, giving them a sweet taste. Conversely in a lowincome sample of infants who received commercial baby foods free of charge as part of a national public health initiative in the US, those who consumed commercial baby food consumed a greater variety of fruits and vegetables [37].…”
Section: Discussionmentioning
confidence: 55%
“…Similarly a study in the US indicated that many parents have a preference for fresh fruits and vegetables over jarred baby foods [32]. Garcia's study [13] comparing home-made baby food to commercial baby food confirmed that the nutritional quality of home-made baby food is generally superior; with the exception of rusks and biscuits, which were higher in iron and calcium than homemade versions, although also higher in sugar. A US study reported that may types of commercial infant and toddler foods had equivalent levels of sodium and sugar to products aimed at older children or adults [33].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Studies with information on the sodium and sugar content of complementary foods sold in the United States are outdated [18][19][20][21] or include few or no toddler foods. [18][19][20][21][22][23][24] Studies conducted in other countries [22][23][24][25][26] may not apply to the nutrient content of foods sold in the United States. National intake recommendations and food regulations differ, for example, between the United States and Canada 27,28 ; different types of food may be offered, and differences in the same type of food may exist.…”
Section: What This Study Addsmentioning
confidence: 99%